Briefer activation time is associated with better outcomes after out-of-hospital cardiac arrest. (October 2016) - Nichol, Graham; Cobb, Leonard A.; Yin, Lihua; Maynard, Charles; Olsufka, Michele; Larsen, Jonathan; McCoy, Andrew M.; Sayre, Michael R.
Abstract: Background: Treatment of out-of-hospital cardiac arrest (OHCA) requires prompt intervention. Better outcomes are associated with briefer time from dispatch of emergency medical services (EMS) providers to arrival on scene, application of a defibrillator or insertion of an advanced airway. We assessed whether time from receipt of a call by a telecommunicator to dispatch of EMS providers was associated with outcomes. Methods: This was a retrospective analysis of a prospective cohort study of persons who had OHCA treated by EMS providers in Seattle, WA. Activation interval was defined as time from call pick up by telecommunicator to notification of EMS providers to respond to the call. Response interval was defined as the time from notification of EMS providers to their arrival at patient side. We determined the association between time intervals and outcomes of sustained restoration of spontaneous circulation (ROSC), survival to hospital discharge and neurologically favorable survival using multiple logistic regression. Secondary analyses assessed the relative contribution of activation versus response interval, and adjusted for post-treatment patient and EMS characteristics. Results: Among 2, 687 patients, activation interval was mean 1.2 ± 0.6 min. Response interval was mean 6.1 ± 2.4 min. 1, 232 (45.9%) achieved ROSC; 475 (17.7%) survived to discharge; and 428 (15.9%) had favorable neurologic status at discharge. Compared to an activation interval of at least 1.5 min, patients with briefer intervals were more likely to survive to discharge (adjusted odds ratio (OR) for <1 min, 1.69 (95% confidence interval (CI), 1.26, 2.28); adjusted odds ratio for 1 to 1.49 min, 1.54 (95% CI, 1.14, 2.08); p value = 0.002). With baseline survival of 10%, the absolute increase in survival associated with a 30 s decrease in activation interval was 0.7% and for a 30 s decrease in response interval was 0.4%. Conclusions: Briefer activation interval was independently associated with greater survival. Further research is needed to assess whether reduction of the activation interval improves outcome after OHCA.